Evaluatıon Du Nıveau De Developpement De Competences Des Etudıants En Lıcence 3 Et Master 1 De Scıences Physıques Des Unıversıtes De Cote D’ıvoıre Sur L’oxydoreductıon - Nguessan, Kouamé (European Scientific Journal, ESJ, 2016)
Successful teaching of the concept of redox by teachers of secondary schools assumes that these latter during their professional training at the Ecole Normale Supérieure d’Abidjan effectively mobilize the concept of redox and basics associated therewith. Therefore, the analysis of the knowledge acquired throughout their academic and academic background, and taking into account the difficulties identified at their level must necessarily be taken into account during the course of their training. We propose in this paper to show the importance of skills mobilized by students in Licence 3 and Master 1 in vocational training, limiting ourselves to the conceptualization of the concept of redox physical sciences. We will seek to identify the skills mobilized on this concept by those responding to the question: the basic knowledge they have, they are sufficient for the efficient and effective training? The research protocol was implemented associated an analysis of responses to the three question types (control, application and reflection) asked students in the explanation and interpretation of efficient and effective classroom activities to them request for their professional training. The results state that these students experience the same types of difficulties. They also observe well in their ability to explain the nature of oxidationreduction reactions at the application of redox principles to electrochemical batteries. It is therefore necessary to mobilize additional resources to make them effective and efficient in high schools and colleges.